Upaya Pencegahan Tindak Kekerasan Melalui Kegiatan Parenting Pada Siswa SDN 227 Margahayu Utara - Warta, Waska; Listianti, Listianti; Palupy, Veranita Intan; Islamiyathi, Winna; Sofayantina, Yanti (Abdimas Indonesian Journal, 2025)
Violence in schools is a serious problem that not only disrupts the teaching and learning process but also has an impact on students' mental, physical, and social health. In an environment that should be safe to learn, many students actually face the threat of violence, both in the form of physical, verbal, and psychological. The purpose of this Community Service is to increase parental participation in preventing violence against children through strengthening positive, effective, and compassionate-based parenting in the family and school environment and also to create a safe, comfortable and fun school environment. This service activity uses a descriptive quantitative approach with a data collection method using questionnaires/surveys. In the service activity, samples were taken in cluster sampling. Location of Community Service at SD Negeri 227 Margahayu Utara, Bandung City. Community service activities will be carried out in the 2024 academic year. The results of community service show that: (1) Parents and teachers of SD Negeri 227 Margahayu Utara, Bandung City, are ready to synergize and implement positive discipline for efforts to prevent violence; (2) Creating a safe, comfortable and fun school environment so that student well-being is achieved; (3) Improving knowledge and skills in accompanying children's growth and development. Parents and teachers play an important role in shaping children's character through parenting with the application of positive discipline, not only helping children grow into confident and independent individuals, but also creating a friendly, inclusive, and bullying-free environment.